High- $Q$ Bound State in the Continuum Cavity Enabled by High-Order Topological Charge - Zhao Zheng; Ye Chen; Feifan Wang; Yi Zuo; Xiaoyu Zhang; Peishen Li; Zihao Chen; Zhiyuan Qian; Zixuan Zhang; Chao Peng (IEEE Photonics Journal)
We propose and demonstrate a high-quality ( $Q$ ) bound state in the continuum (BIC) cavity based on a hexagonal lattice photonic crystal (PhC) slab with $C_{6}$ symmetry, which carries high-order topological charges of $q=-\text{2}$ . By combining the lateral photonic bandgap and high-order topological charge, we realize a $Q$ of $\text{7}× \text{10}^{4}$ in the experiment which is several times higher than traditional BIC cavities with topological charge of $q=±\text{1}$ . Specifically, we found that the boundary orientation would significantly influence the performance of lateral confinement. In contrast to an X direction boundary, a gradient J direction boundary can best alleviate the shortcoming of lateral leakage due to incomplete bandgap and the scattering because of momentum mismatching, and relax the strict constraints on wafer thickness. Our findings could broaden the application of BIC cavities from bio-sensing to on-chip telecommunication.